PENGARUH KUALITAS SISTEM, KUALITAS LAYANAN, DAN KEMUDAHAN PENGGUNAAN TERHADAP KEPUASAN PENGGUNA SISTEM INFORMASI AKUNTANSI - Aisyafira Dienise (2023)
This study aims to determine the effect of system quality, service quality, and ease of use on accounting information system user satisfaction. The population of this study are users of the cashier application system in the FnB business in Depok City. This research uses techniques accidental sampling and obtained 82 cashier application users as respondents, this type of research is quantitative research. The hypothesis was tested using SmartPLS 3.0 software with the partial least square method. The test results show that system quality, service quality, and ease of use have a significant positive effect on user satisfaction of accounting information systems.